Utilization of growth monitoring and promotion services among children younger than 2 years in West Armachiho district, Northwest Ethiopia - Teklemuz, Novel; Sisay, Mekonnen; Baffa, Lemlem Daniel; Mengistu, Berhanu; Atenafu, Azeb (Frontiers in Public Health, 2023)
Introduction: Inadequate physical growth and poor development of children is a prevalent and significant problem worldwide, making 149 million children aged less than five years stunted and 49 million wasted. Growth monitoring and promotion (GMP) is one of the major activities implemented with the aim of capturing growth faltering before the child reaches the status of under-nutrition. In relation to this, Amhara region, where the study area is found, is a highly burdened area in child malnutrition. Thus, it needs further investigation about the GMP services utilization and associated factors among children aged less than two years in the study area.The aim of this study was to assess growth monitoring and promotion services utilization and associated factors among children aged less than two years. Methods:Community-based cross-sectional study was conducted in the West Armachiho district including 703 mother-child pairs with response rate of 94.7%. A simple random sampling technique was used to select the respondents. Both bivariable and multivariable logistic regression analysis was performed. An adjusted odds ratio (AOR) with a 95% confidence interval was used to measure the strength of the association. Results: The proportion of growth monitoring and promotion services utilization in the West Armachiho district was 13. 7% (95%Cl; 11.2, 16.4). Factors such as maternal educational status (AOR=2.17, 95%Cl; 1.05, 4.49), institutional delivery (AOR=3.16, 95%Cl; 1.62, 6.13), family size (AOR=2.66, 95%Cl; 1.13, 6.23), access to health facility (AOR=3.17, 95%Cl; 1.45, 6.95) and maternal knowledge (AOR=4.53, 95%Cl; 2.71, 7.59) were significantly associated with utilization of growth monitoring and promotion services.Utilization of growth monitoring and promotion services in children aged less than two years in the West Armachiho district was low. Thus, giving due attention to the improvement of knowledge of the mothers/caregivers about child GMP services and counseling them about the importance of facility delivery is vital to improve growth monitoring and promotion services in the area.